Introduction to the fractal concept in secondary education using immersive virtual reality - Chavil Montenegro, Dante Yván (2020)
The fractal concept is not introduced in high school  despite its mathematical potential and applicability. Virtual  reality is a tool suitable for the facilitating of such an introduction. Our interest lies in understanding the influence of  the use of NeoTrie VR immersive virtual reality software on  the teaching of the fractal concept to first-year secondary  school students. A descriptive and qualitative research  method is employed, with three groups of students of four  members each. The results show that NeoTrie VR facilitates  the construction of fractals, and we observe that this positively impacts assimilation of the fractal concept. In addition, students display concentration and enjoyment, consistent with the flow experience, when using this software.